2011
DOI: 10.1002/glia.21215
|View full text |Cite
|
Sign up to set email alerts
|

Increased excitatory amino acid transport into murine prion protein knockout astrocytes cultured in vitro

Abstract: Prion protein (PrP) is expressed on a wide variety of cells and plays an important role in the pathogenesis of transmissible spongiform encephalopathies. However, its normal function remains unclear. Mice that do not express PrP exhibit deficits in spatial memory and abnormalities in excitatory neurotransmission suggestive that PrP may function in the glutamatergic synapse. Here we show that transport of D-aspartate, a non-metabolized L-glutamate analog, through excitatory amino acid transporters (EAATs) was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(76 reference statements)
1
8
0
Order By: Relevance
“…These results are supported by several in vitro studies, where expression of PrP C was protective against staurosporine or anisomycin-induced apoptosis [127, 128]. Conversely, loss of PrP C was beneficial against glutamate-induced excitotoxicity in vitro, an effect supposedly mediated by increased uptake of glutamate in PrP C -ablated astrocytes [129]. …”
Section: Possible Neuroprotective Roles Of Prpcsupporting
confidence: 57%
“…These results are supported by several in vitro studies, where expression of PrP C was protective against staurosporine or anisomycin-induced apoptosis [127, 128]. Conversely, loss of PrP C was beneficial against glutamate-induced excitotoxicity in vitro, an effect supposedly mediated by increased uptake of glutamate in PrP C -ablated astrocytes [129]. …”
Section: Possible Neuroprotective Roles Of Prpcsupporting
confidence: 57%
“…To this aim, it would be interesting to investigate the relationship in cultured astrocytes because: (i) Cbl deficiency has been shown to affect mainly astrocytes morphologically and biochemically [10,99,100], and (ii) PrP C s have been shown to modulate astrocyte functions in vitro [101].…”
Section: Discussionmentioning
confidence: 99%
“…This study used Zürich Prnp−/− mice backcrossed on the FVB background and Prnp+/+ FBV controls. In a different study using cultured astrocytes from Edinburgh Prnp−/− mice backcrossed to C57BL/10SnJ, Prnp−/− astrocytes showed more rapid transport of glutamate than Prnp+/+ astrocytes, which correlated with increased protection against glutamate-induced excitotoxicity (Pathmajeyan et al, 2011). These data suggest that Prnp−/− brain cells or tissue might be less sensitive to possible seizure inducing stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…PrP null (Prnp−/−) mice were previously found to be deficient in hippocampal spatial memory (Criado et al, 2005) and also showed reductions in paired pulse facilitation and long-term potentiation in the dentate gyrus (Collinge et al, 1994, Colling et al, 1996, Colling et al, 1997, Curtis et al, 2003, Criado et al, 2005). In addition, lack of PrP has been shown to affect normal physiology of the glutamatergic synapse (Khosravani et al, 2008, Pathmajeyan et al, 2011). Furthermore, deletion of PrP using a Cre-loxP mouse system resulted in reduction of afterhyperpolarization potentials, suggesting a direct role for PrP in the modulation of neuronal excitability (Mallucci et al, 2002).…”
Section: Introductionmentioning
confidence: 99%